2015
DOI: 10.1016/j.ejor.2015.05.067
|View full text |Cite
|
Sign up to set email alerts
|

A minimum cost network flow model for the maximum covering and patrol routing problem

Abstract: a b s t r a c tThis paper shows how the maximum covering and patrol routing problem (MCPRP) can be modeled as a minimum cost network flow problem (MCNFP). Based on the MCNFP model, all available benchmark instances of the MCPRP can be solved to optimality in less than 0.4s per instance. It is furthermore shown that several practical additions to the MCPRP, such as different start and end locations of patrol cars and overlapping shift durations can be modeled by a multi-commodity minimum cost network flow model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…As outlined in Section 3.3, the study of the MCPRP conducted by Dewil et al (2015) demonstrated that the problem is not  -hard as claimed by Keskin et al (2012), where the MCPRP was formulated as an extensive MIP. This highlights a valuable lesson in addressing the computational complexity of a combinatorial optimization problem which can be correctly formulated via different modeling approaches.…”
Section: Mathematical Description Of the Pbspccmentioning
confidence: 97%
“…As outlined in Section 3.3, the study of the MCPRP conducted by Dewil et al (2015) demonstrated that the problem is not  -hard as claimed by Keskin et al (2012), where the MCPRP was formulated as an extensive MIP. This highlights a valuable lesson in addressing the computational complexity of a combinatorial optimization problem which can be correctly formulated via different modeling approaches.…”
Section: Mathematical Description Of the Pbspccmentioning
confidence: 97%
“…Models and algorithms for optimal dynamic allocation of patrol tugs to oil tankers along the northern Norwegian coast General models on resource allocation and patrol routing problems in the literature include p-median problems (p-MP) (Campbell, 1996;Church and ReVelle, 1976;Church et al, 2004;Ishfaq and Sox, 2010), p-center problems (p-CP) (Davidović et al, 2011;Drezner, 1984;Espejo et al, 2015;Suzuki and Drezner, 1996), covering problems that are categorized into maximal covering location problems (MCLP) (Balcik and Beamon, 2008;Church and ReVelle, 1974;Davari et al, 2011), set covering problems (SCP) (Badri et al, 1998;Beasley and Jørnsten, 1992;Caprara et al, 2000), maximum coverage patrol routing problems (MCPRP) (Capar et al, 2015;Dewil et al, 2015;Keskin et al, 2012;Li and Keskin, 2013) and police districting problems (PDP) D'Amico et al, 2002).…”
Section: Related Literaturementioning
confidence: 99%
“…Thus, the problem is finding the cheapest way of sending the city bus from o to d through the network [61,62] while imposing that all the PoI and the pickup/dropout links are visited at least once.…”
Section: Mathematical Model and Solution Methodsmentioning
confidence: 99%